Re‐irradiation of canine non‐lymphomatous nasal tumours using stereotactic radiation therapy (10 Gy x 3) for both courses: Assessment of outcome and toxicity in 11 dogs. (13th February 2022) - Gieger, Tracy L.; Haney, Siobhan M.; Nolan, Michael W.
Abstract: No uniformly beneficial treatments exist for dogs with non‐lymphomatous nasal tumours (NLNT) that relapse after radiotherapy (RT). Reirradiation may prolong survival and improve quality of life. In this retrospective study, we describe outcomes for 11 dogs that had CT‐confirmed locoregional progression of NLNT after an initial course of stereotactic RT (SRT#1; 10 Gy × 3) and were then re‐treated with the same type of protocol (SRT#2, also 10 Gy × 3). The median time between SRT #1 and SRT #2 was 243 days (95% CI: 78–385 days). Ten dogs (91%) had a clinical benefit after SRT#1; five dogs (45%) had clinical benefit after SRT#2. Adverse events after SRT#2 included nasocutaneous or oronasal fistula formation ( N =  3 at 180, 270, and 468 days), seizures ( N =  2 at 78 and 330 days), bacterial or fungal rhinitis ( N =  2 at 240 and 385 days), and facial swelling ( N =  1 at 90 days). All 11 dogs have died, due to disease progression, presumed radiotoxicity, or declining quality of life; in most cases, it was difficult to discern between these conditions. The median overall survival time (OST) from SRT#1 was 745 days (95% CI: 360–1132). The median overall survival time (OST) from SRT #2 was 448 days (95% CI: 112–626). For these dogs, survival was prolonged, but adverse events after SRT#2 were common (8/11; 73%). Therefore, before consenting to re‐irradiation with this protocol, pet owners should be counselled about survivorship challenges, including risk for severe toxicities, and persistence of clinical signs.